Deinstitutionalisation from the perspective of sensemaking: an empirical investigation of the Electricity of Vietnam Corporation - Tham, Huyen Anh (2012)
This thesis is a study of deinstitutionalisation seeking to understand the evolvement of deinstitutionalisation process via the lens of sensemaking. It does so by conducting an in-depth qualitative, case study-based empirical study of the processual nature of deinstitutionalisation and the significance of organisational sensemaking during the deinstitutionalisation process. An interdisciplinary approach is adopted drawing insights from various literatures including institutional theory, sensemaking and social psychology. The need for greater understanding of the deinstitutionalisation phenomenon, especially its process is acknowledged after relevant literatures are reviewed. The potential of using microanalysis in examining the deinstitutionalisation process is demonstrated. The sensemaking perspective is thus used to facilitate this processual research.